Inactivation of enveloped viruses and killing of cells by fatty acids and monoglycerides. - Thormar, H (1987)
Lipids in fresh human milk do not inactivate viruses but become antiviral after storage of the milk for a few days at 4 or 23 degrees C. The appearance of antiviral activity depends on active milk lipases and correlates with the release of free fatty acids in the milk. A number of fatty acids which are normal components of milk lipids were tested against enveloped viruses, i.e., vesicular stomatitis virus, herpes simplex virus, and visna virus, and against a nonenveloped virus, poliovirus. Short-chain and long-chain saturated fatty acids had no or a very small antiviral effect at the highest concentrations tested. Medium-chain saturated and long-chain unsaturated fatty acids, on the other hand, were all highly active against the enveloped viruses, although the fatty acid concentration required for maximum viral inactivation varied by as much as 20-fold. Monoglycerides of these fatty acids were also highly antiviral, in some instances at a concentration 10 times lower than that of the free fatty acids. None of the fatty acids inactivated poliovirus. Antiviral fatty acids were found to affect the viral envelope, causing leakage and at higher concentrations, a complete disintegration of the envelope and the viral particles. They also caused disintegration of the plasma membranes of tissue culture cells resulting in cell lysis and death. The same phenomenon occurred in cell cultures incubated with stored antiviral human milk. The antimicrobial effect of human milk lipids in vitro is therefore most likely caused by disintegration of cellular and viral membranes by fatty acids. Studies are needed to establish whether human milk lipids have an antimicrobial effect in the stomach and intestines of infants and to determine what role, if any, they play in protecting infants against gastrointestinal infections.